2019
DOI: 10.1111/acel.13013
|View full text |Cite
|
Sign up to set email alerts
|

Senescence‐associated tissue microenvironment promotes colon cancer formation through the secretory factor GDF15

Abstract: The risk of colorectal cancer (CRC) varies between people, and the cellular mechanisms mediating the differences in risk are largely unknown. Senescence has been implicated as a causative cellular mechanism for many diseases, including cancer, and may affect the risk for CRC. Senescent fibroblasts that accumulate in tissues secondary to aging and oxidative stress have been shown to promote cancer formation via a senescence‐associated secretory phenotype (SASP). In this study, we assessed the role of senescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 45 publications
3
77
0
Order By: Relevance
“…In humans, GDF15 is expressed in response to cellular damage and serum levels are positively correlated with age (Schafer et al, 2020). GDF15 also associated with senescence to promote colon cancer formation, and human airway epithelial senescence (Guo et al, 2019;Wu et al, 2016). However, secretion of this protein by senescent vascular endothelial cells seemed to be beneficial by promoting function of vascular progenitor (Ha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, GDF15 is expressed in response to cellular damage and serum levels are positively correlated with age (Schafer et al, 2020). GDF15 also associated with senescence to promote colon cancer formation, and human airway epithelial senescence (Guo et al, 2019;Wu et al, 2016). However, secretion of this protein by senescent vascular endothelial cells seemed to be beneficial by promoting function of vascular progenitor (Ha et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that GDF15 could serve as a potential biomarker for EC ( 10 ). GDF15 not only promoted bone metastasis of prostate cancer but also induced colon cancer formation in senescence-associated tissue microenvironment ( 6 , 24 ). However, the role of GDF15 in the invasion and metastasis of EC remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that GDF15 could serve as a potential biomarker for EC [10]. GDF15 not only promoted bone metastasis of prostate cancer but also induced colon cancer formation in senescence-associated tissue microenvironment [6,23]. However, the role of GDF15 in the invasion and metastasis of EC remains poorly understood, with potential mechanisms yet to be deciphered.…”
Section: Discussionmentioning
confidence: 99%